Report on MSR 2005 international workshop on mining software repositories. - Diehl, Stephan
A one-day workshop on the topic of Mining Software Repositories (MSR) was held at ICSE 2005 in St. Louis, Missouri. Researchers and practitioners in the MSR field try to transform static record keeping software repositories to active ones. These repositories permit researchers to gain empirically based understanding of software development, while software practitioners use these repositories to predict and plan various aspects of their project.Following the success of last year's workshop, MSR 2005 had a large number of high quality submissions and a great number of participants. 22 papers were accepted from 38 submissions - 11 papers were presented as Lightning talks (5 mins) and another 11 papers were presented as regular talks (15 mins). The Lighting talks were followed with a walk-around demo and discussion session.This report includes an overview of the presentations made during the day and a summary of the issues raised throughout the workshop.
Keywords: General literature; Introductory and survey; Information systems; Database management; Database administration; Data warehouse and repository; Database applications; Data mining; Design; Documentation